Effect of homeopathic medicines during the initial stage and vegetative development of cucumber plants (Cucumis sativus L.) - Abasolo-Pacheco, Fernando; Ojeda-Silvera, Carlos Michel; García-Gallirgos, Víctor; Melgar-Valdes, Carolina; Nuñez-Cerezo, Karen; Mazón-Suástegui, José Manuel (REVISTA TERRA LATINOAMERICANA, 2020)
The application of bioactive substances in a minimum dose is an alternative to reduce the application of harmful agrochemicals in agriculture, particularly vegetables. The objective of this research was to evaluate the effect of four homeopathic medicines during germination, emergence, and vegetative development of cucumber plants (Cucumis sativus L.). The experimental design included two centesimal homeopathic dynamizations (7CH and 13CH) of Silicea terra (SiT), Natrum muriaticum (NaM), Magnesia phosphorica (MaP), and Arsenicum album (ArA) and a control (water) treatment. A completely randomized 2 × 4 + 1 block design was used in three repetitions. The variables evaluated were rate and percentages of germination and emergence, stem and radicle length, and fresh and dry weight of the aerial part and radicle. Additionally, during the vegetative development the diameter of the stem and the number of leaves and flowers were evaluated. With ArA-13CH, significant differences in germination were observed (53.33%) and with NaM-13CH longer stem length (107.07 cm) during vegetative development, compared to the control group (78.63 cm). Radicle length showed significant differences with the application of SiT-7CH (49.59 cm) compared to the control group (28.6 cm). During germination the best result in the radicle fresh and dry weight was recorded when applying ArA-13CH. In emergence, the greatest fresh radicle weight was obtained with MaP-13CH, and the largest stem diameter, number of leaves and number of flowers were obtained with NaM. The results obtained confirmed that the evaluated homeopathic medicines positively affected the initial stage and vegetative development of cucumber (Cucumis sativus L.) under controlled conditions. This research represents an advance in agricultural homeopathy for the sustainable management of vegetable cultivation.